صور من التكافل الاجتماعي بين ساكنة وادي سوف زمن المحتل الفرنسي (دراسة وثائقية - عثماني, الجباري (جامعة الوادي university of eloued, 2022)
لا ريب أن التكافل الاجتماعي يكرّس أكرم القيم الأخلاقية، بِرّ الانسان لأخيه الانسان، ورحمته به، وإسعافه عند الحاجة؛ حتى يعيش في عز وكرامة. ومن هذا المنطلق سعى الجزائريون في فترة المحتل الفرنسي، والتي فُقِد فيها الأَمْنين من الجوع والخوف، إلى التكاتف والتكافل، من داخل العوائل وخارجها؛ وهو الدافع لدراسة الموضوع في وادي سوف، استنادا لوثائق صادرة عن هيئات قضائية رسمية، ثرية بمادة علمية تُجلي المرغوب، وبعد التحليل والتحقيق، أظهر منطوق العقود بأن مجتمع البحث متراحم متكافل يشدّ بعضه بعضا، يسعى في وجوه الخير، ابتغاء الأجر والثواب من ربه التواب. There is no doubt that social solidarity proves the noblest of moral values, the kindness of man to his fellow man, his mercy towards him, and his assistance when needed. So live in dignity. From this standpoint, the Algerians, during the period of the French occupation, sought interdependence, from within and outside families. It is the impetus to study the issue of solidarity in Wadi Souf, based on documents issued by official judicial bodies, rich in scientific material that clarifies what is desired, After analysis and investigation, the operatives of the contracts showed that the research community is merciful and solidarity striving for goodness, seeking reward and forgiveness
مقال
Keywords: تكافل اجتماعي؛ صدقات؛ تبرعات؛ سلف؛ وقف؛ فقراء